Wings : a history of aviation from kites to the space age - Crouch, Tom D. (Washington, D.C. : Smithsonian National Air and Space Museum, 2003)
This book tells the history of the birth and development of human flight - the technology that defined the 20th century. Tom Crouch weaves the people, machines and ideas of the air age into a narrative and shows how this extraordinary dream was realized.
Includes bibliographical references (p. [677]-690) and index.
Keywords: Aeronautics -- History; Space technology